2021
DOI: 10.1186/s12950-021-00279-3
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 10 and interleukin 10 receptor in paediatric inflammatory bowel disease: from bench to bedside lesson

Abstract: Background The differences between adults and children in inflammatory bowel disease (IBD) phenotype, severity, complications, co-morbidities, and response to the therapy resulted in the extraction of paediatric IBD. It has been revealed that the substantial role in the development of IBD in children under 6 years of age plays a single genetic mutation (monogenic IBD). On the other hand, in older children and adolescents IBD is usually associated with number of interactions between susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 41 publications
(65 reference statements)
0
12
0
1
Order By: Relevance
“…In this way, it can be determined whether a probiotic candidate bacterium can protect cellular permeability while maintaining paracellular TEER values [ 52 , 53 ]. IBD and IBS are associated with an increase in proinflammatory cytokines, such as IL-1β, TNF-α, and IL-8, and an imbalanced IL-10/IL-12 ratio [ 54 , 55 ]; the importance of this status was previously demonstrated in IL-10 −/− mice [ 56 ]. Another key cytokine is IL-8, also known as CXCL8, a CXC-type chemokine originally identified as a leukocyte chemoattractant [ 57 ].…”
Section: Target Screening To Select Bacterial Strains With Probiotic ...mentioning
confidence: 99%
“…In this way, it can be determined whether a probiotic candidate bacterium can protect cellular permeability while maintaining paracellular TEER values [ 52 , 53 ]. IBD and IBS are associated with an increase in proinflammatory cytokines, such as IL-1β, TNF-α, and IL-8, and an imbalanced IL-10/IL-12 ratio [ 54 , 55 ]; the importance of this status was previously demonstrated in IL-10 −/− mice [ 56 ]. Another key cytokine is IL-8, also known as CXCL8, a CXC-type chemokine originally identified as a leukocyte chemoattractant [ 57 ].…”
Section: Target Screening To Select Bacterial Strains With Probiotic ...mentioning
confidence: 99%
“…IL-10 is a key anti-inflammatory cytokine influencing the production of pro-inflammatory mediators and other functions of many immunocompetent cells. Defects in IL-10 signaling have been reported to be associated with IBD, especially in children [7]. IL-19 has been found to inhibit the production of pro-inflammatory cytokines by macrophages, Th1 and Th2 cells and has been suggested to have an anti-inflammatory effect in colitis [8].…”
Section: P R E P R I N Tmentioning
confidence: 99%
“…It is suggested that Th1 and Th17 cells self-limit their inflammatory activity via IL-10 expression [26]. Mutations in IL-10 or its receptor genes have been reported to increase susceptibility to IBD [7,27].…”
Section: P R E P R I N T Of Cd Measurement Of Ifn-γ Is Only For Diffe...mentioning
confidence: 99%
“…IL-10 can act as both an immunosuppressant and immunostimulant, reducing the production of proinflammatory mediators from macrophages and antigen presentation to T cells by dendritic cells (DC), yet activating mast cell, B cell and CD8 T cell proliferation, and increasing interferon γ production and cytotoxic activity. The importance of IL-10 is highlighted by the fact its dysregulation underlies many human diseases, including psoriasis, Crohn’s disease, systemic lupus erythematosus, and asthma [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%